Ansiedad-estado y variables sociodemográficas en futbolistas juveniles colombianos durante competencia (2011)
In order to assess the anxiety state in relation to sociodemographical variables during competitions, players competing in the semifinals of the National Youth Football Championships (n = 93) held in Manizales in August 2009 were evaluated. The test used was Spielberger et ál.'s STAI (IDARE) (1970). The average age of participants was 17,4±2,0 years. The results of STAI were related to sociodemographic variables and athletic performance such as playing position, chronological age and sport, socio-economic strata, education and place of birth. It was found that the defenses, in the team of Valle del Cauca, the higher socioeconomic players (5-6) and the youngest athletes experienced higher levels of anxiety, while according to education, place of origin (capital vs. province) and chronological age differences were not significant.